INFLUENCE OF HEALTH TECHNOLOGY ASSESSMENT AND ITS MEASUREMENT. (26th January 2017) - Hailey, David; Werkö, Sophie; Rosén, Måns; Macpherson, Karen; Myles, Susan; Gallegos Rivero, Verónica; Hipólito-Olivares, Cecilia; Sihvo, Sinikka; Pwu, Jasmine; Yang, Wen-Wen; Chen, Yong-Chen; Perez Galán, Ana; et al.
Abstract : Objectives: The aim of this study was to obtain information on methods used to measure health technology assessment (HTA) influence, decisions that were influenced, and outcomes linked to HTA. Methods: Electronic databases were used to locate studies in which HTA influence had been demonstrated. Inclusion criteria were studies that reliably reported consideration by decision makers of HTA findings; comparative studies of technology use before and after HTA; and details of changes in policy, health outcomes, or research that could be credibly linked to an HTA. Results: Fifty-one studies were selected for review. Settings were national (24 ), regional (12 ), both national and regional (3 ) hospitals (9 ), and multinational (3 ). The most common approach to appraisal of influence was review of policy or administrative decisions following HTA recommendations (51 percent). Eighteen studies (35 percent) reported interview or survey findings, thirteen (26 percent) reviewed administrative data, and six considered the influence of primary studies. Of 142 decisions informed by HTA, the most common types were on routine clinical practice (67 percent of studies), coverage (63 percent), and program operation (37 percent). The most frequent indications of HTA influence were on decisions related to resource allocation (59 percent), change in practice pattern (31 percent), and incorporation of HTA details in reference material (18 percent). Few publications assessed the contribution of HTA to changing patient outcomes. Conclusions: The literature on HTA influence remains limited, with little on longer term effects on practice and outcomes. The reviewed publications indicated how HTA is being used in different settings and approaches to measuring its influence that might be more widely applied, such as surveys and monitoring administrative data.